Peran Perpustakaan Pusat Dinas Sejarah Angkatan Darat Dalam Meningkatkan Literasi Sejarah - Mentari Meilani; Nur Rahmadhani Safitri; Rosiana Nurwa Indah (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2023)
The library is a strategic place in exploring history. This is because the source of information in the form of primary and secondary data is in the library. One of the libraries that contains historical information sources is Central Library of the Army History Service. Since its inauguration, few people have taken advantage of the historical collections in this library. Even though the collection in this library is very informative and there are many rare collections. For this reason, in this study, researchers examine the role of the Central Library of the Army History Service in increasing interest in historical literacy. This study uses a descriptive method with a qualitative approach. The data used comes from primary data and secondary data. The results show that in realizing its role in increasing historical literacy, the library has provided a representative room with various historical literature on various subjects and languages that can be accessed for free. The library also carries out socialization activities in the form of making booklets, active on Instagram and its website. In addition, the library innovated by making the R.P Soewardi T Reading Corner facility. This facility received a positive response from its users which could increase interest in reading. Thus, the Central Library of the Army History Service always tries to optimize its role in providing knowledge about history in order to increase historical literacy in the community.Keywords: role of libraries, historical literacy, Central Library of The Army History Service